1975
DOI: 10.1161/01.str.6.6.638
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid in Cerebral Hemorrhage and Infarction

Abstract: Abstract:Cerebrospinal Fluid in Cerebral Hemorrhage and Infarction• Cerebrospinal fluid (CSF) abnormalities were correlated with pathological diagnoses in 61 patients with autopsy-verified intracerebral hemorrhage or cerebral infarction. Lumbar punctures were performed within one week of onset of symptoms. The CSF color and red blood cell counts were the most useful CSF parameters in differentiating between intracerebral hemorrhage and cerebral infarction. In 75% of the patients with intracerebral hemorrhage, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 7 publications
3
20
0
Order By: Relevance
“…1027 Since red cell counts less than 1,000 may result in clear fluid, attention to the number of red cells may be a more sensitive discriminator. Lee et al 26 found a 26% incidence of absent red cells in HI. Although none of our patients with HI had absent red cells, of eleven spinal fluid examination only three had numbers sufficiently high to be observed as bloody in appearance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…1027 Since red cell counts less than 1,000 may result in clear fluid, attention to the number of red cells may be a more sensitive discriminator. Lee et al 26 found a 26% incidence of absent red cells in HI. Although none of our patients with HI had absent red cells, of eleven spinal fluid examination only three had numbers sufficiently high to be observed as bloody in appearance.…”
Section: Discussionmentioning
confidence: 95%
“…In one autopsy series, 75% of cases with intracerebral hemorrhage, 10% of cases with HI, and no cases with ischemic infarction who had lumbar punctures showed grossly bloody or xanthochromic fluid. 26 In studies comparing CT scan with lumbar puncture in the diagnosis of HI, 10 to 17% of patients with HI on CT had apparently bloody or xanthochromic fluid. 1027 Since red cell counts less than 1,000 may result in clear fluid, attention to the number of red cells may be a more sensitive discriminator.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have provided evidence that supports the role of leukocytes in ICH. Early studies by Molle (1942) and Lee et al (1975) showed that leukocyte counts in cerebrospinal fluid, especially the polymorphonuclear neutrophilic leukocyte counts, were frequently elevated after ICH. Infants with intraventricular hemorrhage also have greater total numbers of leukocytes than infants without On day 3 after ICH induction in mice, infiltrated neutrophils (arrowheads, MPO + , A) and mature macrophages (arrowheads, F4/80 + , C) can be seen near the hematoma.…”
Section: Leukocytesmentioning
confidence: 99%
“…16 -53~M Although hemorrhagic infarction is frequently noted at autopsy in patients with cerebral embolism it is difficult to detect clinically. CT scan and lumbar puncture may not be helpful in establishing the presence of hemorrhagic infarction, 31 -39 -59 -61 particularly when these procedures are done early, before the hemorrhagic aspect of the infarct has time to develop. The hemorrhagic component of the infarction probably evolves over several days following the onset of the stroke 36 - 37 and it follows that the diagnostic value of lumbar puncture and CT scan would be enhanced if they were obtained after a delay of a few days.…”
Section: Therapeutic Considerationsmentioning
confidence: 99%